Recommendations for running injuries - Pope, D.; Barton, C. J.; Lehman, G. (British Journal of Sports Medicine, 2019)
Based on Physio Edge podcast 059 with Tom Goom (stomgoom), Greg Lehman and Dr Christian Barton (La Trobe Sport and Exercise Medicine Research Centre, Bundoora Australia)